Performance Comparison Amil Zakat Institutions Managed By The Government And Private Organization In West Sumatra Province - Husni Shabri; Nurul Huda (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2014)
This paper aimed to compare the performance of Amil Zakat Board and Amil Zakat Institutions in managing zakat funds in the region of West Sumatra province, based on data in 2010. The Comparisons were made by measuring the performance of these two institutions which include five aspects of assessment namely 1) Performance of Shariah compliance, legality and institutional 2) Performance of Management 3) Financial Performance 4) Performance of economic empowerment and 5) Performance Social Legitimacy. The research was conducted with surveys and interviews using a questionnaire to four Amil Zakat Board and four Amil Zakat institutions. This study used the Mann Whitney U Test to see the significance of the difference. The results of analysis showed that significant difference between performance of zakat management at Amil Zakat Board and Amil Zakat Institutions in West Sumatera Province. The performance of Amil Zakat Board is better than the performance of Amil Zakat Institutions especially financial performance and the performance of social legitimacy.